Penerjemahan Indonesia-Arab pada Petunjuk Keselamatan Penerbangan Komersial - Hasfikin, Hasfikin; Nisa, Ainy Khairun (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
The main issue in this research is the form of Indonesian-Arabic translation of commercial aviation safety instructions. The research method used in the research is descriptive analysis using data collection techniques by recording documents. The results of the research show that the Indonesian-Arabic translation technique for safety instructions on commercial aircraft consists of 12 data in the form of words and phrases, consisting of 6 data translated using literal translation techniques, 1 datum using applied translation techniques, 3 data using common translation techniques, 2 data data using modulation translation techniques.